Beggar-thy-neighbour tax cuts: Mobility after a local income and wealth tax reform in Switzerland - Isabel Martínez (ETH Zurich, KOF Swiss Economic Institute, 2021)
I analyze mobility responses to the unique introduction of regressive local income schedule in the Swiss Canton of Obwalden in 2006, which was aimed at attracting the top 1%. Differencein-Differences estimations comparing Obwalden to all other cantons confirm that the reform successfully attracted rich taxpayers: by 2016, the share of rich in the canton more than doubled and average income per taxpayer was 16% higher relative to 2005. Using individual tax data and an instrumental variable approach, I find a large elasticity of the stock of rich taxpayers of 1.5-2 with respect to the average net-of-tax rate. The corresponding flow elasticity ranges from 6.5 to 10. However, the reform did not yield any Laffer effects. Finally, I find positive effects on local employment: the number of jobs per 1,000 inhabitants rose by an estimated 2.3% relative to other cantons and compared to 2005. However, these employment effects are likely driven by a simultaneous reduction of the corporate tax rate.
hdl:20.500.11850/463387
Keywords: H24; H31; H71; H73; R23; 330; Mobility; Personal income tax; Local taxes; Tax competition; Regressive income tax